Proceedings of the Third Workshop on Abusive Language Online 2019
DOI: 10.18653/v1/w19-3516
|View full text |Cite
|
Sign up to set email alerts
|

A Platform Agnostic Dual-Strand Hate Speech Detector

Abstract: Hate speech detectors must be applicable across a multitude of services and platforms, and there is hence a need for detection approaches that do not depend on any information specific to a given platform. For instance, the information stored about the text's author may differ between services, and so using such data would reduce a system's general applicability. The paper thus focuses on using exclusively text-based input in the detection, in an optimised architecture combining Convolutional Neural Networks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Three studies compared character-level, word-level, and hybrid (both character- and word-level) CNNs, but drew completely different conclusions. Park (2018) and Meyer & Gambäck (2019) found hybrid and character CNN to perform best respectively. Probably most surprisingly, Lee, Yoon & Jung (2018) observed that word and hybrid CNNs outperformed character CNN to similar extents, with all CNNs performing worse than character n-gram logistic regression.…”
Section: Obstacles To Generalisable Hate Speech Detectionmentioning
confidence: 99%
“…Three studies compared character-level, word-level, and hybrid (both character- and word-level) CNNs, but drew completely different conclusions. Park (2018) and Meyer & Gambäck (2019) found hybrid and character CNN to perform best respectively. Probably most surprisingly, Lee, Yoon & Jung (2018) observed that word and hybrid CNNs outperformed character CNN to similar extents, with all CNNs performing worse than character n-gram logistic regression.…”
Section: Obstacles To Generalisable Hate Speech Detectionmentioning
confidence: 99%
“…Their argument for adopting the traditional approach was to provide better explainability of the knowledge transfer between domains. Some other studies adopted several neural-based models, including convolutional neural networks (CNN) [75,141], long short-term memory (LSTM) [8,75,92,94,145], bidirectional LSTM (Bi-LSTM) [115], and gated recurrent unit (GRU) [27]. The most recent works focus more on investigating transferability or generalizability of stateof-the-art transformer-based models such as Bidirectional Encoder Representations from Transformers (BERT) [19,48,66,79,83,90,92,134] and its variant like RoBERTa [48] in the cross-domain abusive language detection task.…”
Section: Modelsmentioning
confidence: 99%
“…[134] Neural model This study proposed several LSTM-based models that only focuses on using text information (char n-grams and word embedding) representation for building platform-agnostic hate speech detector, but they did not conduct any cross or multidomain experiment to evaluate their model. [75] Transformer based Experimented with a BERT-based classifier and topic modeling approach, which show that removing domain-specific instances improve the model's out-domain performance [83] Neural based Proposed several representations including target, content, and linguistic behavior and used cross attention gate flow to refine these representations, providing better domain-transfer knowledge.…”
Section: Modelsmentioning
confidence: 99%
“…For the most part, word-level n-grams have been highly predictive, with other linguistic features such as part-of-speech tags (Xu et al, 2012;Davidson et al, 2017) and sentiment score (Van Hee et al, 2015;Davidson et al, 2017) providing slight improvements. Due to their ability to perform better in an online setting where spelling errors and adversarial behaviour are commonplace, character-level features have been endorsed , and also shown to often be superior to word-level information for this task (Meyer and Gambäck, 2019). Metadata about users have also been used as features: Waseem and Hovy (2016) claim gender information leads to improved performance, while Unsvåg and Gambäck (2018) report user-network data to be more important.…”
Section: Previous Workmentioning
confidence: 99%